Circuits and Systems for the Internet of Things : CAS4IoT. - Goes, João (Tutorials in Circuits and Systems Ser., 2017)
Internet-of-Things (IoT) can be envisaged as a dynamic network of interconnected physical and virtual entities ("things"), with their own identities and attributes, seamlessly integrated in order to e.g. actively participate in economic or societal processes, interact with services, and react autonomously to events while sensing the environment. By enabling things to connect and becoming recognizable, while providing them with intelligence, informed and context based decisions are expected in a broad range of domains spanning from health and elderly care to energy efficiency, either providing business competitive advantages to companies, either addressing key social concerns. The level of connectivity and analytical intelligence provided by the IoT paradigm is expected to allow creating new services that would not be feasible by other means. This CAS4IoT book targets post-graduate students and design engineers, with the skills to understand and design a broader range of analog, digital and mixed-signal circuits and systems, in the field of IoT, spanning from data converters for sensor interfaces to radios, ensuring a good balance between academia and industry, combined with a judicious selection of worldwide distinguished authors.